2016
DOI: 10.1039/c6ra11748a
|View full text |Cite
|
Sign up to set email alerts
|

Mapping gold nanoparticles on and in edible leaves in situ using surface enhanced Raman spectroscopy

Abstract: The increased prevalence of engineered nanomaterials (ENPs) in the environment and their potential toxicity require study on whether those engineered nanomaterials could possibly contaminate agricultural food and products. However, many techniques require invasive and complicated sample preparation procedures to detect and characterize engineered nanomaterials in complex matrices. Here, we present a non-destructive and label-free approach based on surface enhanced Raman spectroscopic (SERS) mapping technique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Though a growing number of studies are emerging on NP interactions with terrestrial plants, available analytical techniques and associated sample pretreatment methods are limited for assessing the NPs within biological tissues. Some of the most frequently used detection techniques for NPs in plant tissues are electron microscopy (EM), X-ray absorption spectroscopy (XAS), surface enhanced Raman scattering (SERS), and total elemental analysis methods. An early study used 2.8 nm Alizarin red S-bound (ARS) TiO 2 NPs to test the uptake potential in Arabidopsis seedlings . However, the surface sites of these TiO 2 NPs were saturated with sucrose before ARS-labeling, which may have modified the NP uptake potential.…”
Section: Introductionmentioning
confidence: 99%
“…Though a growing number of studies are emerging on NP interactions with terrestrial plants, available analytical techniques and associated sample pretreatment methods are limited for assessing the NPs within biological tissues. Some of the most frequently used detection techniques for NPs in plant tissues are electron microscopy (EM), X-ray absorption spectroscopy (XAS), surface enhanced Raman scattering (SERS), and total elemental analysis methods. An early study used 2.8 nm Alizarin red S-bound (ARS) TiO 2 NPs to test the uptake potential in Arabidopsis seedlings . However, the surface sites of these TiO 2 NPs were saturated with sucrose before ARS-labeling, which may have modified the NP uptake potential.…”
Section: Introductionmentioning
confidence: 99%
“…SERS technique allows the in situ detection of dimethoate on apples without the need for pesticide extraction using AuNPs as the substrate. AuNPs were used as SERS substrates in this study due to their low cytotoxicity and good biocompatibility. Our previous studies demonstrated that the AuNP mirror substrate was able to improve the sensitivity and reproducibility of the detection due to its more uniform distribution than AuNPs. Thus, the AuNP mirror was applied as a SERS substrate in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that NPs are capable of crossing plant mechanical barriers (e.g. cuticle and cell walls) with further translocation [6][7][8]. Moreover, NPs surfaces are easily modifiable with a variety of coatings and, similar to drug delivery, NP surface properties can theoretically be tuned to deliver them to specific leaf structures or tissues in plants [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf itself is covered with a layer of hydrophobic epicuticular waxes [11,12]. In general, there are three main natural pathways how NPs could penetrate cuticle layerstomates, trichomes and pores [6,7,9].…”
Section: Introductionmentioning
confidence: 99%